Electrospun Propolis-coated PLGA Scaffold Enhances the Osteoinduction of Mesenchymal Stem Cells - Askari, Mohammad; Jadid Tavaf, Maryam; Ghorbani, Masoud; Yazdanian, Mohsen; Moghaddam, Mehrdad M. (Current Stem Cell Research & Therapy, 2024)
Background: Major injuries that are caused by trauma and cancer can not be repaired through bone remodeling. The goal of bone regeneration by tissue engineering approaches is to fabricate bone implants in order to restore bone structure and functions. The use of stem cells and polymer scaffolds provides the conditions for tissue regeneration based on tissue engineering. Objective: This study aimed to fabricate a combined matrix of poly(lactide-co-glycolide) (PLGA) and propolis extract, which is a mixture of pollen and beeswax collected by bees from certain plants and has long been used in traditional herbal medicine, to promote the osteogenic differentiation of human adipose- derived mesenchymal stem cells (AD-MSCs). Methods: The scaffold was fabricated through electrospinning and was immersed in a propolis extract solution. Then, AD-MSCs were cultured and differentiated into the osteogenic lineage. The cell viability on the scaffold was evaluated by MTT assay. Osteogenic differentiation of the seeded stem cells was detected by evaluating calcium content, alkaline phosphatase (ALP) activity, and the expression of bonespecific genes. Results: The viability of cells was not affected by propolis-coated and uncoated fabricated scaffolds, while higher calcium content, ALP activity, and expression of RUNX-2, type I collagen, osteocalcin, and osteonectin were observed in cells differentiated on propolis-coated PLGA scaffold on days 7, 14, and 21 of differentiation compared to PLGA scaffold. Conclusion: The results of this study showed that the presence of propolis in the scaffold could lead to better cell attachment and strengthen the osteoinduction process in stem cells.
Keywords: adipose-derived mesenchymal stem cells